Increasing Follicular and Stromal Cell Proliferation in Cryopreserved Human Ovarian Tissue after Long-Term Precooling Prior to Freezing: In Vitro versus Chorioallantoic Membrane (CAM) Xenotransplantation. Issue 11 (November 2013) - Isachenko, Vladimir; Isachenko, Evgenia; Mallmann, Peter; Rahimi, Gohar
A positive effect on the future development of cells, which have been cooled to low suprazero temperatures and then thawed, has been observed before and is not new. The aim of this study was to test the effectiveness of postthawing culture of human ovarian tissue, which was either frozen just after operative removal or cooled after removal to 5°C for 24 h before cryopreservation. Ovarian fragments from six patients were divided into small pieces in the form of cortex with medulla and randomly divided into the following four groups: Group 1 consisted of pieces that just after removal had been cultured in vitro for 8 days in a big volume of medium with mechanical agitation; Group 2 included pieces cooled after operation to 5°C for 24 h and then cultured in vitro for 8 days; Group 3 was comprised of pieces frozen–thawed just after operation and then cultured for 5 days in the chorioallantoic membrane (CAM) culture system; and the pieces in Group 4 were cooled after operation to 5°C for 24 h, frozen–thawed, and then cultured in the CAM system for 5 days. The effectiveness of the tissue culture was evaluated by the development of follicles and by the intensiveness of proliferation in the tissue (by expression of cytokeratin and Ki-67). For Groups 1, 2, 3, and 4, the mean densities of follicles per 1 mm 3 was 12.9, 12.2, 12.4, and 16.1, respectively ( p 1–2 > 0.1; p 3–4 < 0.05). For these groups, 87%, 95%, 71%, and 84% of the preantral follicles were morphologically normal ( p 1–2, 3–4 < 0.05). The immunohistochemical analysis showed increased proliferation after cooling of fresh and cryopreserved tissue. Long-term (24 h) cooling of ovarian tissue to 5°C before cryopreservation increases the viability of the cells in the tissue after thawing. Additionally, the efficacy of the CAM system for the culture of thawed human ovarian tissue was demonstrated.